Pembangunan Sistem Informasi Penjualan Kopi berbasis Web (Studi Kasus : Remboeg Pawon Group) - Alvinanda Rosha Kurniawan; Adam Hendra Brata; Eriq Muhammad Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Coffee shops are one of the businesses in the culinary field. At first the coffee shop was created to serve various kinds of coffee servings for coffee lovers. One of the coffee business activists in Malang is Remboeg Pawon Group. Remboeg Pawon does not yet have an online system to monitor the results of sales and the existing stock of goods. There may also be a discrepancy in the calculation for profit which causes confusion in reporting to investors. With these problems, the authors want to create a Web-Based Cashier and Goods Management System at Remboeg Pawon Group. Which can help manage Remboeg Pawon Group and can convince investors. The system used by researchers is the Point of Sale or POS System. In this study the authors used white-box testing and black-box testing. White-box testing is a test where program tests are based on knowledge of the program structure and its components. Some of the categories tested in black-box testing include functions that are not in accordance with functionality or functions that are missing interfaces, data structures, behavior (behavior) and initialization and termination. In unit and integration testing, several functions were obtained which were tested with the class driver on the methods in the program code and found the results presented in the test case with the test case results that matched the needs. And the validation test obtained from the 52 functions from the results of the previous requirements was declared valid and in accordance with the needs.